Woolly stops the train - Amery, Heather; Cartwright, Stephen, 1947-; Tyler, Jenny (London : Usborne ; Tulsa, OK : EDC, 1999)
Sheep on railroad tracks make a train stop and then they get on board the train.
Woolly stops the train -- The Grumpy goat.
Two stories one book.
K-3.
Keywords: Animals -- Fiction; Railroads -- Trains -- Fiction; Board books for children